Effect of Metabolic Acidosis on QT Intervals in Patients with Chronic Kidney Disease. Issue 6 (June 2016) - Yenigun, Ezgi Coskun; Aypak, Cenk; Turgut, Didem; Aydin, Mehmet Zafer; Dede, Fatih
Background: There is a strong association between chronic kidney disease (CKD) and cardiovascular events. Increased arrhythmia risk in kidney disease is one of the main predominant factors in increased mortality and sudden cardiac death. To estimate this risk, noninvasive measurement of repolarization abnormalities including QT interval and its heart rate-corrected value (QTc) with surface ECG, are commonly used parameters in clinical practice. The aim of this study is to examine the effect of CKD-related problems – mainly acidosis – on QT intervals. Methods: 30 patients with stage 3–5 CKD whose serum bicarbonate concentrations below 20 mmol/L were included in the study. Alkali therapy with oral sodium bicarbonate was used to maintain the serum bicarbonate concentration in the normal range. At the beginning all patients had sinus rhythm on surface ECG records. Kidney function tests including serum urea, serum creatinine, uric acid, blood gas analysis, and electrolytes were analyzed at the beginning and at the end of alkali treatment. All patients underwent 12 lead-ECGs, recorded simultaneously. One cardiologist examined the ECGs manually in terms of QT intervals, corrected for heart rate (QTc), QT dispersion (QTd) and corrected QT dispersion (QTcd). Results: There were statistically significant differences in QT intervals, QTc, QTd and QTcd before and after sodium bicarbonate treatment. The correlation analyses revealed that there were significant negative correlations in pretreatment ECGs of patients between QTd and QTcd with blood pH level. Multivariate analyses between biochemical parameters and QTd-QTcd intervals have revealed that pH was related to QTd and QTc. Conclusions: This study demonstrated that QT intervals on surface ECG are decreased after treatment of acidosis in CKD. Further studies are needed to show whether increased QT intervals cause ventricular arrhythmias in CKD.